"In Sunshine and Joy"?: The Story of Medem Sanatorium in Miedzeszyn. (February 2014) - Kozłowska, Magdalena
Medem Sanatorium in Miedzeszyn was one of the most famous establishments of TSYSHO, the Central Yiddish School Organization, in interwar Poland. Although not officially associated with the Bund, it unofficially promoted Bundist ideals through its teaching staff. This article aims to examine the educational methods of Medem Sanatorium in Miedzeszyn. Medem served as a central space for Bundist ideology, attracting such figures as Polish radical socialist Wanda Wasilewska, and hosting, among others, a young Marek Edelman, the future leader of the Warsaw ghetto uprising. Showing the activities and struggles of the institution the author touches different problems of the Polish interwar period: the entanglement of Bundist ideology, everyday life, religious practices, and, last but not least, politics towards Yiddish. Ultimately, the author underlines that the Medem Sanatorium was a part of a broader action concentrated on creating a new secular Jewish culture.